2017
DOI: 10.1016/j.joca.2017.02.792
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal extrusion and bone marrow lesions are associated with incident and progressive knee osteoarthritis

Abstract: The presence of baseline meniscal extrusion and BMLs are associated with incident and progressive knee of each other (OA) and represent important structural targets for the treatment and prevention of knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 31 publications
3
57
0
1
Order By: Relevance
“…ME is a risk factor for cartilage loss and knee osteoarthritis. [15][16][17] For this reason, it is a challenge for surgeons to prevent or diminish graft or implant extrusion in patients undergoing meniscal substitutions. Different methods have been described to prevent extrusion in MAT.…”
Section: Discussionmentioning
confidence: 99%
“…ME is a risk factor for cartilage loss and knee osteoarthritis. [15][16][17] For this reason, it is a challenge for surgeons to prevent or diminish graft or implant extrusion in patients undergoing meniscal substitutions. Different methods have been described to prevent extrusion in MAT.…”
Section: Discussionmentioning
confidence: 99%
“…TKA, total knee arthroplasty [Color figure can be viewed at wileyonlinelibrary.com] significant baseline radiographic OA. Conversely, in the setting of existing OA, Raynauld et al 12 and Teichtahl et al 13 found medial extrusion rather than lateral extrusion to be a predictor of TKA. In the nonarthritic knee, prior biomechanical studies have demonstrated that due to increased asymmetry of lateral compartment cartilage surfaces, the lateral meniscus bears a greater percentage of lateral compartment loads (approximately 70%) than the medial meniscus bears for the medial compartment (approximately 50%).…”
Section: Independent Association Between Meniscal Status and Risk Omentioning
confidence: 97%
“…10,11 Meniscal extrusion, which is often but not always secondary to a meniscal tear, has also been associated with increased cartilage volume loss in the setting of existing OA, 11,12 as well as with middle-aged adults without radiographic OA. 13 Meniscal root tears cause a disruption of hoop forces and an increase in tibiofemoral contact pressures equivalent to that of a total meniscectomy. 3,7,8 Root tears can be difficult to diagnose on magnetic resonance imaging (MRI), 10,14 though meniscal extrusion may be a useful indirect indication of a root tear as over 50% of patients with evidence of a medial meniscus extrusion on imaging also had a medial meniscus root tear.…”
mentioning
confidence: 99%
“…For example, clinical follow‐up studies have demonstrated that partial lateral meniscectomy, particularly in patients with posterior root partial meniscectomies, are at higher risk for the development of OA than are medial PM patients . Bone marrow lesions (BMLs) have been reported in association with meniscus pathology, providing further evidence of the important role of the meniscus in joint contact mechanics, and such BMLs have also been associated with cartilage degeneration and OA progression, particularly in cases with meniscal extrusion or axial malalignment …”
Section: Mechanical Predictors Of the Response To Partial Meniscectomymentioning
confidence: 99%